Lithium-rich manganese-based positive electrode material based on morphology design, preparation method of lithium-rich manganese-based positive electrode material, lithium ion battery positive plate and lithium ion battery
By designing the lithium -rich manganese -based positive pole material with layers and lithium -enriched phases, the use of specific lithium sources and front -drive Moorebi and sintering conditions to form a secondary particle structure, solving the volume ratio caused by the deficiency of the existing material structure, the volume ratio capacity The problem of poor low and cycle stability achieves higher volume than capacity and cycle stability.
Patent Information
- Application Number
- CN202411418260.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing lithium-rich manganese-based positive electrode materials have structural defects, resulting in low volume specific capacity and poor circulation stability of lithium-ion batteries.
By designing a lithium-rich manganese-based cathode material with a layered phase and a lithium-rich phase, and using specific molar ratios of lithium source and precursor and sintering conditions, a secondary particle structure composed of multiple primary particles is formed.
Improve the structural stability and compact density of the positive pole material, and enhance the volume ratio of the lithium -ion battery to the volume ratio and cycle stability.
Smart Images

Figure CN119361672A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium-rich manganese-based positive electrode material based on morphology design and a preparation method thereof, a lithium-ion battery positive electrode sheet and a lithium-ion battery. Background Art
[0002] Traditional polymorphic (PC) lithium-manganese-rich layered cathode materials (LMR) have high discharge specific capacity (>260mAh / g) and are considered to be strong competitors for the next generation of high-energy lithium-ion battery cathode materials. However, due to the many intrinsic defects in lithium-manganese-rich cathode materials, it is difficult to obtain widespread commercial applications. These defects include but are not limited to low unit cell density due to the presence of Li2MnO3 phase, which further leads to low volume energy density; poor kinetic performance; severe pressure drop effect caused by phase transition from layered phase to spinel phase; generation of microcracks between crystals, etc. The single-crystal SC-LMR positive electrode material has received extensive attention. The SC-LMR material has dispersed micron-level primary particles, which greatly reduces the specific surface area of the LMR material, which is beneficial to inhibiting the performance degradation caused by the infiltration of the electrolyte into the bulk phase of the material; secondly, the dispersed primary particles effectively alleviate the anisotropic volume deformation between the agglomerated primary particles, thereby reducing the risk of microcracks; further, due to the reduction in specific surface area and the reduction in ineffective pores between particles, the compaction density of the material is greatly improved, thereby increasing the volume energy density of the LMR material.
[0003] However, SC-LMR materials still have inevitable disadvantages, such as the increased particle size further prolongs the Li + The diffusion distance of LMR further deteriorates its Li + At the same time, since the bond energy of Mn-O is much higher than that of Ni / Co-O, and there are more Mn-O bonds in LMR materials, the SC morphology is difficult to synthesize, and higher synthesis temperature or more complex synthesis method is often required to provide higher energy. The higher energy in the synthesis stage leads to the Li + / Ni 2+ The intensification of the mixing phenomenon, the Ni in the Li layer 2+ Further hindering Li + diffusion, which will lead to Li + The generation of concentration gradients deteriorates the structural stability of the material and causes performance degradation in subsequent cycles.
[0004] CN117747806A discloses a lithium-rich manganese-based positive electrode material and its precursor and preparation method, a lithium-ion battery and electrical equipment. The precursor is prepared by a solution coprecipitation method, and the oxide primary particles obtained by pre-sintering are smaller in particle size and have more primary particle gaps, which is beneficial to the subsequent sintering of Li + Diffusion; and the subsequent high-temperature sintering of lithium hydroxide has a lower decomposition temperature, which can decompose Li + , penetrate into the secondary particles earlier to react, change the grain boundaries and structure, and improve the charging capacity. However, due to the small primary particles and more gaps, the specific surface area of the material is large, and the compaction density is difficult to improve, so it has no effect on improving the volume energy density; and in the subsequent battery cycles, it is more susceptible to the infiltration of electrolyte, resulting in particle cracking and capacity decay.
[0005] Therefore, there is an urgent need to develop a positive electrode material and a lithium-ion battery made from the positive electrode material that performs well in terms of volumetric capacity and cycle stability. Summary of the invention
[0006] The purpose of the present invention is to overcome the structural defects of the lithium-rich manganese-based positive electrode materials in the prior art, which lead to the problems of low volumetric capacity and poor cycle stability of the lithium-ion batteries prepared therefrom, and to provide a lithium-rich manganese-based positive electrode material based on morphology design and a preparation method thereof, a lithium-ion battery positive electrode sheet and a lithium-ion battery.
[0007] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a lithium-rich manganese-based positive electrode material, wherein the positive electrode material contains lithium and manganese, the positive electrode material contains a layered phase and a lithium-rich phase, and the positive electrode material includes a plurality of secondary particles, and the secondary particles are formed by the aggregation of a plurality of primary particles.
[0008] A second aspect of the present invention provides a method for preparing a lithium-rich manganese-based positive electrode material, wherein the method comprises:
[0009] The lithium source and the precursor are mixed and sintered to obtain a positive electrode material;
[0010] Wherein, the molar ratio of the lithium source to the precursor is (1.55-1.75):1;
[0011] The sintering process includes: heating from room temperature to 500-650°C at a heating rate of 3-7°C / min, pre-sintering for 2-8h, heating to 920-980°C at a heating rate of 3-7°C / min, and sintering for 8-14h.
[0012] The third aspect of the present invention provides a lithium-rich manganese-based positive electrode material prepared by the above preparation method.
[0013] A fourth aspect of the present invention provides a lithium-ion battery positive electrode sheet, wherein the lithium-ion battery positive electrode sheet comprises the above-mentioned lithium-rich manganese-based positive electrode material.
[0014] A fifth aspect of the present invention provides a lithium ion battery, comprising the above-mentioned lithium ion battery positive electrode sheet.
[0015] Through the above technical solution, the technical solution provided by the present invention achieves the following beneficial effects:
[0016] (1) The positive electrode material provided by the present invention contains lithium and manganese, and the positive electrode material contains a layered phase and a lithium-rich phase. The positive electrode material includes a plurality of secondary particles, and the secondary particles are formed by the mutual aggregation of a plurality of primary particles, so that the positive electrode material has excellent structural stability and no cracks in the crystal, and the lithium-ion battery made of the positive electrode material has excellent volumetric capacity and cycle stability.
[0017] (2) The method for preparing the positive electrode material provided by the present invention affects the structure and performance of the positive electrode material by controlling the molar ratio of the lithium source to the precursor and the sintering conditions. The preparation method is simple and safe, low in cost, and has good continuity, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a SEM schematic diagram of the positive electrode materials prepared in Example 1 and Comparative Examples 4 and 5;
[0019] Figure 2 It is a schematic diagram of the first cycle charge and discharge curves of the positive electrode materials prepared in Example 1, Comparative Example 4 and Comparative Example 5;
[0020] Figure 3 Schematic diagram of discharge specific capacity curves of the positive electrode materials prepared in Example 1, Comparative Example 4 and Comparative Example 5 at different current rates;
[0021] Figure 4 It is a schematic diagram of the 100-cycle retention rate curve of the positive electrode materials prepared in Example 1, Comparative Example 4 and Comparative Example 5;
[0022] Figure 5 is a schematic diagram of XRD of the positive electrode materials prepared in Example 1 and Comparative Example 3;
[0023] Figure 6 It is a SEM schematic diagram of the positive electrode materials prepared in Example 1 and Comparative Examples 4 and 5 after 100 cycles. DETAILED DESCRIPTION
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0025] A first aspect of the present invention provides a lithium-rich manganese-based positive electrode material, wherein the positive electrode material contains lithium and manganese, and the positive electrode material contains a layered phase and a lithium-rich phase; the positive electrode material includes a plurality of secondary particles, wherein the secondary particles are formed by agglomeration of a plurality of primary particles.
[0026] In the present invention, the XRD spectra of the positive electrode materials prepared in Example 1 and Comparative Example 3 are Figure 5 It can be seen that the positive electrode material contains a layered phase and a lithium-rich phase. In the XRD spectrum of the positive electrode material, there are diffraction peaks at 2θ of 17°-18°, 36°-37°, 43°-45°, 48°-49°, 58°-59°, 64°-65°, 65°-66° and 68°-69°, indicating the presence of a layered phase; in the XRD spectrum of the positive electrode material, there is a diffraction peak at 2θ of 20°-25°, indicating the presence of a lithium-rich phase. It can also be seen from the XRD spectrum of the positive electrode material provided by the present invention that the positive electrode material does not contain other crystalline structures (no other diffraction peaks). If the positive electrode material contains other crystalline structures, such as the formation of a rock salt phase, due to the Li in the rock salt phase + Diffusion sites will be occupied by transition metals, which will hinder the Li + diffusion, thus causing the electrochemical performance to deteriorate.
[0027] In the present invention, there are no cracks in the positive electrode material crystals (obtained from SEM morphology observation). If there are cracks in the positive electrode material crystals, the cracks will cause the electrolyte to penetrate into the bulk phase, further react with the bulk phase material, and corrode the positive electrode material, causing battery capacity decay.
[0028] According to the present invention, the positive electrode material has a chemical composition represented by the following general formula: xLi2MnO3·(1-x)LiMO2, wherein M is at least one of Ni, Co and Mn, 0 <x<1。
[0029] According to the present invention, the compaction density of the lithium-rich manganese-based positive electrode material is 3-4 g / cm 3 , preferably 3.2-3.5g / cm 3 .
[0030] In the present invention, when the compaction density of the lithium-rich manganese-based positive electrode material does not meet the above range, the compaction density is less than 3g / cm3 When the active material particles and the conductive agent particles have pores between each other, it is not conducive to the conduction of ions and electrons; the compaction density is greater than 4g / cm 3 When rolling, the positive electrode material will produce cracks due to excessive rolling, which is not conducive to the battery cycle performance.
[0031] In the present invention, the positive electrode material is solid, and the solid form is particles, preferably irregular particles. The particles have a secondary particle structure formed by a plurality of primary particles agglomerated with each other, such as Figure 1 As shown in (a) in the figure. The primary particles are composite oxides containing lithium and manganese, and the secondary particles are composite oxides containing lithium and manganese. The primary particles have a strip-like morphology, and then a plurality of the primary particles agglomerate with each other, such as a plurality of primary particles agglomerate in a mortise-and-tenon connection, to form the secondary particles, which have an irregular appearance.
[0032] According to the present invention, the primary particles have a stripe-like morphology.
[0033] According to the present invention, the average length of the primary particles is 1-4 μm, preferably 2.5-3 μm.
[0034] According to the present invention, the average width of the primary particles is 0.4-0.8 μm, preferably 0.5-0.7 μm.
[0035] According to the present invention, the average aspect ratio of the primary particles is 5-6, preferably 5.2-5.8.
[0036] In the present invention, the primary particles have a strip-like morphology, and then agglomerate to form secondary particles with irregular shapes, so that the formed positive electrode material can provide good performance improvement. Further, when the average length, average width and average aspect ratio of the primary particles are limited to meet the above ranges, firstly, the specific surface area of the positive electrode material is reduced, and the structure is stable, which is conducive to suppressing the performance attenuation caused by the infiltration of the electrolyte into the body phase of the positive electrode material; secondly, the dispersed primary particles effectively alleviate the anisotropic volume deformation generated between the agglomerated primary particles and the structure is stable, thereby reducing the risk of microcracks; finally, due to the reduction of the specific surface area and the reduction of the ineffective pores between the particles, the compaction density of the positive electrode material is greatly improved, thereby improving the volume energy density of the positive electrode material.
[0037] In the present invention, the average length and width of the primary particles are measured using a scanning electron microscope model S-4800 produced by Hitachi.
[0038] According to the present invention, the average particle size of the secondary particles is 4-7 μm, preferably 5-6 μm.
[0039] In the present invention, the average particle size of the secondary particles is measured using a laser particle size analyzer.
[0040] In a preferred embodiment of the present invention, the positive electrode material contains lithium and manganese, the positive electrode material is a layered phase and a lithium-rich phase, and the positive electrode material includes a plurality of secondary particles, and the secondary particles are formed by agglomeration of a plurality of primary particles;
[0041] Wherein, the compaction density of the positive electrode material is 3.3-3.4g / cm 3 ;
[0042] The average particle size of the primary particles is 2.7-2.8 μm.
[0043] A second aspect of the present invention provides a method for preparing a lithium-rich manganese-based positive electrode material, wherein the method comprises:
[0044] The lithium source and the precursor are mixed and sintered to obtain a positive electrode material;
[0045] Wherein, the molar ratio of the lithium source to the precursor is (1.55-1.75):1;
[0046] The sintering process includes: heating from room temperature to 500-650°C at a heating rate of 3-7°C / min, pre-sintering for 2-8h, heating to 920-980°C at a heating rate of 3-7°C / min, and sintering for 8-14h.
[0047] In the present invention, when the molar ratio of the lithium source to the precursor and the sintering conditions meet the above range, the positive electrode material can have good morphology and structural integrity, contain a layered phase and a lithium-rich phase, and do not contain other impurities, so that the battery has excellent electrochemical properties.
[0048] According to the present invention, the room temperature is 25-35°C.
[0049] Furthermore, the molar ratio of the lithium source to the precursor is (1.6-1.7):1.
[0050] Further, the temperature is raised from room temperature to 550-620°C at a heating rate of 4-6°C / min, pre-sintered for 3-7h, and then raised to 940-960°C at a heating rate of 4-6°C / min, and sintered for 10-12h.
[0051] According to the present invention, the lithium source is selected from LiOH and / or Li2CO3.
[0052] According to the present invention, the precursor is selected from Ni 0.19 Co 0.1 Mn 0.675 (OH)2、Ni 0.25 Mn0.75 (OH)2、Ni 0.2 Co 0.1 Mn 0.7 (OH)2 and Ni 0.1625 Co 0.1625 Mn 0.675 At least one of (OH)2.
[0053] According to the present invention, the mixing conditions include: a rotation speed of 1300-1700 rpm and a time of 3-7 min.
[0054] Furthermore, the mixing conditions include: a rotation speed of 1400-1600 rpm and a time of 4-6 min.
[0055] The third aspect of the present invention provides a lithium-rich manganese-based positive electrode material prepared by the above preparation method.
[0056] A fourth aspect of the present invention provides a lithium-ion battery positive electrode sheet, wherein the lithium-ion battery positive electrode sheet comprises the above-mentioned lithium-rich manganese-based positive electrode material.
[0057] According to the present invention, a method for preparing a positive electrode sheet for a lithium-ion battery comprises the following steps:
[0058] The positive electrode material, conductive agent (Super P / acetylene black), and binder (PVDF-polyvinylidene fluoride) were weighed and mixed evenly according to a mass ratio of 8:1:1, and then an appropriate amount of NMP was added as a dispersant to prepare a slurry, which was coated on aluminum foil, dried, and cut into pieces to make a positive electrode sheet for a lithium-ion battery.
[0059] A fifth aspect of the present invention provides a lithium ion battery, comprising the above-mentioned lithium ion battery positive electrode sheet.
[0060] According to the present invention, a method for preparing a lithium ion battery comprises the following steps:
[0061] A lithium-ion battery positive electrode sheet including a positive electrode material is used, a metal lithium sheet is used as the negative electrode, a Celgard2500 separator is used, and the main components of the electrolyte are 1 mol / L LiPF6 as the solute and a mixed liquid of dimethyl carbonate, diethyl carbonate, and ethylene carbonate in a volume ratio of 1:1:1 as the solvent. The button batteries are assembled in an argon atmosphere glove box.
[0062] The present invention will be described in detail below by way of examples. In the following examples,
[0063] The morphology of the cathode material was measured using a Hitachi S-4800 scanning electron microscope;
[0064] XRD: obtained by using Rigaku's D / MAX-2500 / pc test;
[0065] The volumetric capacity and cycle performance of the battery were measured using the Landian Test System (LAND CT 2001A) tester of Wuhan Landian Electronics Co., Ltd.
[0066] The raw materials used in the examples and comparative examples are all commercially available.
[0067] Example 1
[0068] LiOH and Ni with a molar ratio of 1.65:1 were added 0.19 Co 0.1 Mn 0.675 (OH)2 was mixed at a rotation speed of 1500 rpm for 5 min, then the temperature was increased from 30 °C to 550 °C at a heating rate of 5 °C / min. After pre-sintering for 5 h, the temperature was increased to 950 °C at a heating rate of 5 °C / min and sintered for 12 h to obtain the positive electrode material (KML)A1.
[0069] Example 2
[0070] Li2CO3 and Ni with a molar ratio of 1.6:1 0.2 Co 0.1 Mn 0.7 (OH)2 was mixed at a rotation speed of 1600 rpm for 6 min, then heated from 35 °C to 620 °C at a heating rate of 6 °C / min. After pre-sintering for 4 h, the temperature was increased to 960 °C at a heating rate of 6 °C / min and sintered for 10 h to obtain the positive electrode material (KML) A2.
[0071] Example 3
[0072] LiOH and Ni with a molar ratio of 1.7:1 were added 0.1625 Co 0.1625 Mn 0.675 (OH)2 was mixed at a rotation speed of 1400 rpm for 4 min, then heated from 25 °C to 550 °C at a heating rate of 4 °C / min. After pre-sintering for 4 h, the temperature was increased to 940 °C at a heating rate of 4 °C / min and sintered for 13 h to obtain the positive electrode material (KML) A3.
[0073] Comparative Example 1
[0074] The positive electrode material was prepared according to the method of Example 1, except that the heating rate was 10° C. / min, to obtain positive electrode material (KML) D1.
[0075] Comparative Example 2
[0076] The positive electrode material was prepared according to the method of Example 1, except that the heating rate was 15° C. / min, to obtain positive electrode material (KML) D2.
[0077] Comparative Example 3
[0078] The positive electrode material was prepared according to the method of Example 1, except that the molar ratio of the lithium source to the precursor was 1.4:1, and the heating rate was 15° C. / min, to obtain the positive electrode material (KML) D3.
[0079] Comparative Example 4
[0080] Li2CO3 and Ni with a molar ratio of 0.79:1 0.19 Co 0.1 Mn 0.675 CO3, mixed at a rotation speed of 1600 rpm for 6 min, then heated from 35 °C to 450 °C at a heating rate of 5 °C / min, pre-sintered for 5 h, then heated to 900 °C at a heating rate of 5 °C / min, and sintered for 12 h to obtain the positive electrode material (PC) D4.
[0081] Comparative Example 5
[0082] (1) Take LiOH and Ni with a molar ratio of 1.65:1 0.25 Mn 0.75 (OH)2, first half of the LiOH and Ni 0.25 Mn 0.75 (OH)2, mixed at a rotation speed of 1500 rpm for 5 min, then heated from 30°C to 600°C at a heating rate of 5°C / min, pre-sintered for 5 h, then heated to 935°C at a heating rate of 5°C / min, and sintered for 5 h to obtain an intermediate powder particle material;
[0083] (2) The remaining half of LiOH was mixed with the intermediate powder particle material at a rotation speed of 1500 rpm for 5 min, and then the temperature was increased from 30°C to 600°C at a heating rate of 5°C / min. After pre-sintering for 5 h, the temperature was increased to 950°C at a heating rate of 5°C / min and sintered for 12 h to obtain the positive electrode material (SC) D5.
[0084] Test Example 1
[0085] The physical properties of the positive electrode materials in the above embodiments were tested.
[0086] The compaction density of the cathode material was measured using a micrometer screw instrument;
[0087] The average particle size of the primary particles was measured using a laser particle size analyzer; the results are shown in Table 1.
[0088] Table 1. Test results of positive electrode material characteristics
[0089]
[0090] Table 1 (continued)
[0091]
[0092] Test Example 2
[0093] The positive electrode materials (A1-A3 and D1-D5) prepared in Example 13 and Comparative Examples 1-5 were subjected to electrochemical performance tests. The results are shown in Table 2.
[0094] Assembling Li-ion Batteries:
[0095] (1) Weighing positive electrode materials (A1-A3 and D1-D5), conductive agent (Super P / acetylene black), and binder (PVDF-polyvinylidene fluoride) in a mass ratio of 8:1:1, mixing them evenly, adding an appropriate amount of NMP as a dispersant to prepare a slurry, coating it on aluminum foil, drying it, and cutting it into pieces to make a positive electrode sheet for a lithium-ion battery;
[0096] (2) A lithium-ion battery positive electrode sheet including a positive electrode material is used, a metal lithium sheet is used as the negative electrode, a Celgard2500 separator is used, and the main components of the electrolyte are 1 mol / L LiPF6 as the solute and a mixed liquid of dimethyl carbonate, diethyl carbonate, and ethylene carbonate in a volume ratio of 1:1:1 as the solvent. The button cells (A1-A3 and D1-D5) are assembled in an argon atmosphere glove box.
[0097] The constant current charge and discharge test of the battery is carried out using the Landian test system (CT2001A LAND) tester of Wuhan Landian Electronics Co., Ltd. The test method is as follows:
[0098] The test was carried out in a 30 degree Celsius constant temperature box, with a current rate of 0.1C (1C = 250mA) and a charge and discharge test in the voltage range of 2-4.8V.
[0099] Data analysis with attached diagram:
[0100] Figure 1 is a SEM schematic diagram of the positive electrode materials prepared in Example 1, Comparative Example 4 and Comparative Example 5, Figure 1 It can be seen that Figure 1 Figure (a) is a SEM schematic diagram of the positive electrode material prepared in Example 1. It can be seen that the primary particles are in the shape of long strips, and the primary particles are connected to each other in a mortise and tenon shape to form secondary particles; Figure 1 Figure (b) is a SEM schematic diagram of the positive electrode material prepared in Comparative Example 4, from which it can be seen that the primary particles are agglomerated into spherical secondary particles; Figure 1 Figure (c) is a SEM schematic diagram of the positive electrode material prepared in Comparative Example 5. It can be seen that the primary particles are independently dispersed and spherical, and are not agglomerated into secondary particles, which are called "single crystals".
[0101] Figure 2 Schematic diagram of the first cycle charge and discharge curves of the positive electrode materials prepared in Example 1, Comparative Example 4 and Comparative Example 5. Figure 2 It can be seen that the volumetric capacity of Example 1 is 886.6 mAh / cm 3 Comparative Example 4 has many pores due to its smaller primary particles, resulting in a lower compaction density and a volumetric capacity of 702.4 mAh / cm 3 Comparative Example 5 has a large grain size and unstable structure, which leads to the attenuation of electrochemical performance, and the volume capacity is 600.3mAh / cm 3 .
[0102] Figure 3 Schematic diagram of the discharge capacity curves of the positive electrode materials prepared in Example 1, Comparative Example 4 and Comparative Example 5 at different current rates. Figure 3 It can be seen that at a relatively low current rate (0.1C-1C), the positive electrode material prepared in Example 1 with primary particles of micron level size and the positive electrode material prepared in Comparative Example 4 with primary particles of nanometer level size have similar discharge specific capacities, while at a higher current rate (2C, 5C), the electrochemical performance of Example 1 is superior to that of Comparative Example 1; while the electrochemical performance of Comparative Example 5 is poor at current rates from low to high, proving that its particle size is large and its structure is unstable, thus affecting the electrochemical performance.
[0103] Figure 4 100-cycle retention rate curves of the positive electrode materials prepared in Example 1, Comparative Example 4 and Comparative Example 5 are shown in FIG. Figure 4 It can be seen that the positive electrode material prepared in Example 1 and the positive electrode material prepared in Comparative Example 2 with micron-level primary particles have excellent cycle stability, while the positive electrode material prepared in Comparative Example 4 shows obvious capacity decay. This is because the primary particles are too small, resulting in an increase in ineffective pores between the materials. During the cycle, the electrolyte will erode the bulk phase of the material along these pores, and then side reactions will occur, which is not conducive to the stability of the cycle. Secondly, in the process of lithium insertion and extraction, anisotropic volume deformation will occur if the primary particles of the material are too small. This anisotropic deformation continues to accumulate, resulting in stress gradients between the materials, thereby posing a risk of cracking.
[0104] Figure 5 is a schematic diagram of XRD of the positive electrode materials prepared in Example 1 and Comparative Example 3. Figure 5It can be seen that in the XRD spectrum of the positive electrode material prepared in Example 1, 2θ has diffraction peaks at 17°-18°, 36°-37°, 43°-45°, 48°-49°, 58°-59°, 64°-65°, 65°-66° and 68°-69°, i.e., a layered phase; in the XRD spectrum of the positive electrode material, 2θ has a diffraction peak at 20°-25°, i.e., a lithium-rich phase; the positive electrode material prepared in Example 1 does not contain other crystalline structures, while the positive electrode material prepared by rapid heating in Comparative Example 3 contains other crystalline structures, such as the formation of a rock salt phase, due to the Li + Diffusion sites will be occupied by transition metals, which will hinder the Li + diffusion, resulting in the degradation of electrochemical performance.
[0105] Figure 6 is a SEM diagram of the positive electrode materials prepared in Example 1, Comparative Example 4 and Comparative Example 5 after 100 cycles. Figure 6 It can be seen that Figure 6 Figure (a) is a SEM schematic diagram of the positive electrode material prepared in Example 1 after 100 cycles. It can be seen that no cracks are generated after 100 cycles; Figure 6 Figure (b) is a SEM schematic diagram of the positive electrode material prepared in Comparative Example 4 after 100 cycles. It can be seen that obvious intercrystalline cracks are generated in the secondary particles, and intracrystalline cracks and crystal plane slips are also generated in the primary particles; Figure 6 Figure (c) is a SEM schematic diagram of the positive electrode material prepared in Comparative Example 5 after 100 cycles, and it can be seen that intracrystalline cracks have occurred.
[0106] Table 2 Electrochemical performance test results
[0107]
[0108] pass Figure 1-5 As can be seen from the results in Table 1-2, the lithium ion batteries prepared in Examples 1-3 of the present invention have excellent electrochemical properties, with a first-week discharge capacity of up to 253.3 mAh / g, a first-week coulombic efficiency of 75.3%, and a first-week volumetric capacity of up to 886.6 mAh / cm 3 .
[0109] Compared with Examples 1-3, Comparative Examples 1-2 use heating rates of 10°C / min and 15°C / min, respectively. The positive electrode material obtained by rapid heating contains other crystalline structures, such as the formation of rock salt phase. + Diffusion sites will be occupied by transition metals, which will hinder the Li + diffusion, resulting in the degradation of electrochemical performance.
[0110] Compared with Examples 1-3, in Comparative Example 3, the molar ratio of lithium source to precursor is 1.4:1, and the heating rate is 15°C / min, which makes the positive electrode material have poor morphology and low structural integrity. In addition to the layered phase and lithium-rich phase, it also contains other impurities-rock salt phase. + Diffusion sites will be occupied by transition metals, which will hinder the Li + diffusion, which reduces the electrochemical performance of the battery.
[0111] Compared with Examples 1-3, in Comparative Example 4, the temperature is first raised to 450°C and then to 900°C to obtain a positive electrode material (PC). Because the primary particles are too small, the ineffective pores between the materials increase. During the cycle, the electrolyte will erode the bulk phase of the material along these pores, and then side reactions will occur, which is not conducive to the stability of the cycle; secondly, in the process of lithium insertion and extraction, the primary particles of the material are too small, and anisotropic volume deformation will occur. This anisotropic deformation continues to accumulate, resulting in a stress gradient between the materials, thereby posing a risk of cracking; the electrochemical performance of the battery is reduced.
[0112] Compared with Examples 1-3, the positive electrode material (SC) prepared in Comparative Example 5 using a different preparation method has an unstable structure because the primary particles are independently dispersed and spherical and do not agglomerate into secondary particles, thereby reducing the electrochemical performance of the battery.
[0113] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A lithium-rich manganese-based positive electrode material, characterized in that: The positive electrode material contains lithium and manganese, contains a layered phase and a lithium-rich phase, and includes a plurality of secondary particles, wherein the secondary particles are formed by agglomeration of a plurality of primary particles.
2. The positive electrode material according to claim 1, wherein The positive electrode material has a chemical composition represented by the following general formula: xLi2MnO3·(1-x)LiMO2, wherein M is at least one of Ni, Co and Mn, <x<1。 3. The positive electrode material according to claim 1 or 2, wherein The compaction density of the positive electrode material is 3-4 g / cm 3 , preferably 3.2-3.5g / cm 3 ; and / or, the primary particles have a stripe-like morphology; Preferably, the average length of the primary particles is 1-4 μm, preferably 2.5-3 μm; and / or, the average width of the primary particles is 0.4-0.8 μm, preferably 0.5-0.7 μm; and / or, the average aspect ratio of the primary particles is 5-6, preferably 5.2-5.8; And / or, the average particle size of the secondary particles is 4-7 μm, preferably 5-6 μm.
4. A method for preparing a lithium-rich manganese-based positive electrode material, characterized in that: The method comprises: The lithium source and the precursor are mixed and sintered to obtain a positive electrode material; Wherein, the molar ratio of the lithium source to the precursor is (1.55-1.75):1; The sintering process includes: heating from room temperature to 500-650°C at a heating rate of 3-7°C / min, pre-sintering for 2-8h, heating to 920-980°C at a heating rate of 3-7°C / min, and sintering for 8-14h.
5. The preparation method according to claim 4, wherein The molar ratio of the lithium source to the precursor is (1.6-1.7):1; And / or, the sintering process includes: heating from room temperature to 550-620°C at a heating rate of 4-6°C / min, pre-sintering for 3-7h, heating to 940-960°C at a heating rate of 4-6°C / min, and sintering for 10-12h.
6. The preparation method according to claim 4 or 5, wherein: The lithium source is selected from LiOH and / or Li2CO3; And / or, the precursor is selected from Ni 0.19 Co 0.1 Mn 0.675 (OH)2、Ni 0.25 Mn 0.75 (OH)2、Ni 0.2 Co 0.1 Mn 0.7 (OH)2 and Ni 0.1625 Co 0.1625 Mn 0.675 At least one of (OH)2.
7. The preparation method according to any one of claims 4 to 6, wherein: The mixing conditions include: a rotation speed of 1300-1700 rpm and a time of 3-7 min; Preferably, the mixing conditions include: a rotation speed of 1400-1600 rpm and a time of 4-6 min.
8. A lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 4 to 7.
9. A positive electrode sheet for a lithium-ion battery, characterized in that: The lithium-ion battery positive electrode sheet comprises the lithium-rich manganese-based positive electrode material as described in any one of claims 1-3 and 8 above.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Lithium-rich manganese-based anode material, preparation method thereof and lithium ion battery containing anode material
CN106910887A
A manganese-based carbonate precursor, a lithium-rich manganese-based cathode material, and a lithium-ion secondary battery
CN114933337A
Lithium-rich manganese-based positive electrode material, preparation method thereof and lithium ion battery
CN117691099A
Lithium-rich manganese-based positive electrode material, precursor and preparation method thereof, lithium ion battery and electric equipment
CN117747806A
Lithium-deficient lithium-rich manganese-based layered oxide positive electrode material and preparation method thereof
CN118039894A